Proceedings of the 2005 Particle Accelerator Conference
DOI: 10.1109/pac.2005.1591378
|View full text |Cite
|
Sign up to set email alerts
|

Status of the CAMD Light Source

Abstract: In parallel with the increasing diversity of its research program, the CAMD Light Source has improved its beam brightness and quality. Using a well calibrated model of the lattice, the ring optic has been refined to generate a lower beam emittance of 150 nm.rad and this has been confirmed by measuring the beta values with the modulated quadrupole shunt system. The beam sizes have also been measured with an X-ray pinhole camera and compared to the calculated emittance. The beam orbit is corrected to a standard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…It would be beneficial to increase the source brightness but the storage ring is already operating with a reduced horizontal emittance of about 150 nm.rad and this cannot be significantly improved [4]. It has therefore been concluded that increasing the source flux is the only option and a MPW would be capable of giving almost an order of magnitude increase.…”
Section: Introductionmentioning
confidence: 99%
“…It would be beneficial to increase the source brightness but the storage ring is already operating with a reduced horizontal emittance of about 150 nm.rad and this cannot be significantly improved [4]. It has therefore been concluded that increasing the source flux is the only option and a MPW would be capable of giving almost an order of magnitude increase.…”
Section: Introductionmentioning
confidence: 99%